ORGANIZATION OF ACTIVITIES AND PERSONNEL COMPOSITION OF THE PRISON IN THE TOWN OF WIŚNICZ, KRAKÓW VOIVODSHIP, II RZECZPOSPOLITA (SELECTED ASPECTS) - RAZYHRAYEV, Oleh; BOROVYK , Andrii (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
After World War I, in the countries of Central and Eastern Europe an integral part of the state-building processes was the formation of penal service (penitentiary system) – an integral component of any state law enforcement system. Interwar Poland – the Second Polish-Lithuanian Commonwealth (II Rzeczpospolita) was no exception, where even before the declaration of independence restoration, the formation processes of penitentiary system were traced. The purpose of the article is to study selected aspects of activities organization and personnel composition of the prison in the town of Wiśnicz, Kraków Voivodeship of II Rzeczpospolita. The research methodology is based on the use of general scientific and specifically historical research methods, including problem-chronological, synchronous, diachronic, comparative and historical, etc. The scientific novelty consists in the fact that the authors attempted, based on unpublished archival materials, to highlight selected aspects of the organization of activities and personnel composition of the prison in the town of Wiśnicz, Kraków Voivodeship in II Rzeczpospolita. Conclusions. Thus, the prison in Wiśnicz was an integral part of the penitentiary system of II Rzeczpospolita. Between the two world wars, this prison evolved from one of the largest penal institutions of the state to the prison of a new profile – “a prison – a craft institution” with broad resocialization opportunities. The penitentiary institution under study was designed to imprison 580 people, but it was often overcrowded and on the eve of World War II there were almost 860 people. During the period under analysis this prison was headed by S. Sledzewski, under whose leadership numerous assistants, inspectors, guards, and office employees worked. The prison staff also included auxiliary personnel – doctors, teachers, and clergy. The staffing level of the prison in Wiśnicz was around 90 – 100 people and was insufficient for the proper functioning of this institution due to its constant overcrowding. At the same time, the prison employees tried to perform their duties properly, which is confirmed by the documentary materials we have analyzed. Key words: Poland, Wiśnicz, prison, penitentiary system, organization, personnel.